The scope and limits of content externalism - Rowlands, Mark (Externalism, 2003)
Content externalism threatens the idea of first-person authority in all its forms, and does so because it calls into question the idea that the access one have to own mental states is privileged in the way required for such authority. Donald Davidson develops an influential argument in favour of the compatibilism of content externalism and first-person authority. Tyler Burge has also attempted to reconcile content externalism with first-person authority. The incompatibility of content externalism and first-person authority is thought to derive from, or be reflected in, the collective mutual inconsistency of three propositions. Content externalism is thought by many to be incompatible with first-person authority. Attempts to reconcile the two positions along compatibilist lines fail and a qualified incompatibilism is the best option. Content externalism does not apply to cognitive architecture, cognitive processes and sensations. Therefore, such externalism does not rule out first-person authority over these sorts of item.